Exergoeconomic analysis and multi‐objective whale optimization of an integrated solid oxide fuel cell and energy storage system using liquefied natural gas cold energy. (9th September 2022) - Wu, Jingjing; Pan, Zhen; Binama, Maxime; Shang, Liyan; Zhou, Li
Summary: A multigeneration system comprising solid oxide fuel cell, compressed air energy storage, gas turbine, supercritical CO2 recompression Brayton cycle (S‐CO2 ), and organic flash Rankine cycle (OFRC) based on liquefied natural gas cold energy is proposed. The system integrates peak shaving, heating, cooling, power generation, and energy storage, solving the imbalance between the supply and demand of renewable energy. It is comprehensively analyzed from the thermodynamic, economic, and exergoeconomic perspectives to evaluate the performance of the three phases (full time, charging period, and discharging period). The evaluation shows that the exergy analysis of the multigeneration system alone is not comprehensive, and the exergoeconomic analysis is more necessary. Additionally, the S‐CO2 coupled with the OFRC generates power in a more efficient way than the S‐CO2 coupled with the Organic Rankine cycle (ORC) or Organic Flash cycle (OFC) does. Finally, the NSGA‐II and multi‐objective whale algorithms are employed to optimize the system. The results show that the multi‐objective whale algorithm is slightly better than the NSGA‐II. Moreover, the optimized round‐trip efficiency ( RTE ) and levelized cost of electricity ( LCOE ) are 68.64% and 0.053 kWh −1, respectively. Compared with the base design point, the RTE improves by 1.93%, and the LCOE decreases by 3.64%. Abstract : A novel multigeneration system based on liquefied natural gas cold energy is established, which follows the principle of "parallel temperature and gradient energy utilization." The effects of three different bottom cycles on system performance are compared. The NSGA‐II and multi‐objective whale algorithms are employed to optimize the system. Compared with the base point, the round‐trip efficiency increased by 1.93%, and the levelized cost of electricity decreased by 3.64%. The system's discharging power generation efficiency is 10.44% higher than a single SOFC‐GT system.